The book that held her heart - Lawrence, Mark, 1966- (Lawrence, Mark, 1966- Library trilogy, 2025)
"Two people once connected by a vast and mysterious library are now separated and must overcome time and distance to reunite and bring peace to their worlds... The fate of an infinite library hangs on one book, a book that holds the power to break the unbreakable. In the face of such forces, fragile things like hearts, family, and the world seem certain to fail. The people most vital to Livira are scattered across time and space, lost, divided into factions, in mortal peril. Somehow, she must bring them together and resolve the unresolvable argument that fuels the library's war. The bond between Livira and Evar has stretched and stretched again. Can it hold at the end, when things fall apart? Can it bring them together against impossible odds? This is the last chapter, the final page. The end threatens and no one, not characters, readers, or even the author, will emerge unscathed"--